Bactericidal antibiotic-phytochemical combinations against methicillin resistant Staphylococcus aureus - Kyaw,Bhone Myint (2012)
Methicillin resistant Staphylococcus aureus (MRSA) infection is a global concern nowadays. Due to its multi-drug resistant nature, treatment with conventional antibiotics does not assure desired clinical outcomes. Therefore, there is a need to find new compounds and/or alternative methods to get arsenal against the pathogen. Combination therapies using conventional antibiotics and phytochemicals fulfill both requirements. In this study, the efficacy of different phytochemicals in combination with selected antibiotics was tested against 12 strains of S. aureus (ATCC MRSA 43300, ATCC methicillin sensitive S. aureus or MSSA 29213 and 10 MRSA clinical strains collected from National University Hospital, Singapore). Out of the six phytochemicals used, tannic acid was synergistic with fusidic acid, minocycline, cefotaxime and rifampicin against most of strains tested and additive with ofloxacin and vancomycin. Quercetin showed synergism with minocycline, fusidic acid and rifampicin against most of the strains. Gallic acid ethyl ester showed additivity against all strains in combination with all antibiotics under investigation except with vancomycin where it showed indifference effect. Eugenol, menthone and caffeic acid showed indifference results against all strains in combination with all antibiotics. Interestingly, no antagonism was observed within these interactions. Based on the fractional inhibitory concentration indices, synergistic pairs were further examined by time-kill assays to confirm the accuracy and killing rate of the combinations over time. The two methods concurred with each other with 92% accuracy and the combinatory pairs were effective throughout the 24 hours of assay. The study suggests a possible incorporation of effective phytochemicals in combination therapies for MRSA infections.